Substance Use Motives as Mediators of the Associations between Self-Control Constructs and Negative Substance Use Consequences: A Cross-Cultural Examination - Montgomery, Zannie (2024)
The present study sought to examine three distinct research questions: a) are self-control constructs (i.e., negative/positive urgency, self-regulation, and emotion-regulation) indirectly related to negative alcohol/marijuana consequences via substance use motives, b) to what extent are these indirect effects consistent across differing drugs (i.e., alcohol and marijuana), and c) are these models invariant across gender and countries. Participants were 2,230 college students (mean age=20.28, SD=0.40; 71.1% females) across 7 countries (USA, Canada, Spain, England, Argentina, Uruguay, and South Africa) who consumed alcohol and marijuana in the last month. Two (one for alcohol and one for marijuana) fully saturated path models were conducted, such that indirect paths were examined for each self-control construct and substance use motive on negative consequences (e.g., negative urgency → coping motives → negative consequences) within the same model. Within the comprehensive alcohol model, we found that lower selfregulation and higher negative urgency/suppression were related to more alcohol consequences via highercoping and conformity motives. For marijuana, we found that lower self-regulation and higher negative urgency/suppression were related to more marijuana consequences via higher coping motives (not significant for conformity motives). Unique to marijuana, we did find support for higher expansion motives indirectly linking positive urgency to more negative consequences. These results were invariant across gender groups and only minor differences across countries emerged. Prevention and intervention programs of alcohol and marijuana around university campuses may benefit from targeting self-control related skills in addition to motives to drug use to prevent and reduce negative drug-related consequences